Empowerment and satisfaction in a multinational study of routine clinical practice - Clarke, E.; Pusch, B.; Jordan, H.; Williams, P.; Konrad, J.; Kawohl, W.; Bär, A.; Rössler, W.; Del Vecchio, V.; Sampogna, G.; Nagy, M.; Süveges, A.; et al. (Wiley, 2015)
Objective: Decision-making between mental health clinicians and patients is under-researched. We tested whether mental health patients are more satisfied with a decision made (i) using their preferred decision-making style and (ii) with a clinician with the same decision-making style preference.